Validation of the Malay version of the life events checklist for DSM-5 among Malaysian undergraduates - Tan, Yee Kee; Siau, Ching Sin; Chan, Lai Fong; Kõlves, Kairi; Zhang, Jie; Ho, Meng Chuan; Chua, Bee Seok; Sulong, Rose Manisah; Bono, Suzanna A.; Fitriana, Mimi; Jamaludin, Abdul Latiff Bin Hj; Maswan, Norfaizadatul Akma Binti Mohamad; et al. (Elsevier, 2023)
This cross-sectional study aimed to validate the Life Events Checklist for DSM-5 (LEC-5) among Malaysian undergraduates (N = 500; mean age = 21.66 ± 1.57), of which 90.4% had ever experienced a lifetime traumatic event. Cronbach's alpha of .87 (95% CI [.86, .89]) and McDonald's omega of .89 (95% CI [.89, .93]) indicated good reliability. Confirmatory factor analysis based on a six-factor structure showed the best fit. The measurement invariance showed that the six-factor structure was similar across sexes. Therefore, the Malay LEC-5 is a valid and reliable instrument to screen for traumatic events among Malaysian undergraduates.